Immune state is associated with natural dietary variation in wild mice Mus musculus domesticus. (22nd May 2019) - Taylor, Christopher H.; Young, Stuart; Fenn, Jonathan; Lamb, Angela L.; Lowe, Ann E.; Poulin, Benoit; MacColl, Andrew D. C.; Bradley, Janette E.
Abstract: The ability, propensity and need to mount an immune response vary both among individuals and within a single individual over time. A wide array of parameters has been found to influence immune state in carefully controlled experiments, but we understand much less about which of these parameters are important in determining immune state in wild populations. Diet can influence immune responses, for example when nutrient availability is limited. We therefore predict that natural dietary variation will play a role in modulating immune state, but this has never been tested. We measured carbon and nitrogen stable isotope ratios in an island population of house mice Mus musculus domesticus as an indication of dietary variation, and the expression of a range of immune‐related genes to represent immune state. After accounting for potential confounding influences such as age, sex and helminth load, we found a significant association between carbon isotope ratio and levels of immune activity in the mesenteric lymph nodes, particularly in relation to the inflammatory response. This association demonstrates the important interplay between diet and an animal's response to immune challenges, and therefore potentially its susceptibility to disease. Aplain language summary is available for this article. Abstract : Plain Language Summary